Intentions of Generation Z Students to Visit Green Hotels in Jabodetabek within the Framework of the Theory of Planned Behaviour and Green Perceived Value - Ardianto, Ari; Prasetya, Prita (Dinasti International Journal of Education Management and Social Science, 2025)
This study examines the determinants of Generation Z students' intention to visit green hotels in the Jabodetabek region, grounded in the Theory of Planned Behaviour and Green Perceived Value. The research employs a quantitative approach, collecting data from 111 respondents through structured questionnaires and analysing it using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that functional value, emotional value, and social value significantly influence attitudes toward green hotels, which in turn positively shape visit intention. Functional value strengthens attitudes through perceptions of service quality, reliability, and cost efficiency, while emotional value reinforces satisfaction, pride, and a sense of moral responsibility. Social value further enhances acceptance and positive social image, particularly among Generation Z, who are highly influenced by community opinions and digital social interactions. Moreover, attitude emerges as a critical determinant of visit intention, confirming the theoretical premise that favourable evaluations of green hotels lead to a stronger behavioural intention. This study contributes to the understanding of sustainable consumer behaviour by highlighting how multidimensional perceived values drive positive attitudes and visit intentions toward green hotels. The results provide theoretical insights for future hospitality research and practical implications for hotel managers in promoting sustainable tourism practices.